The Effect of Using the Explosion Box Medium on the Literacy Skills of 5-6 Year Old Children - Lia, Lia Ulfa Sari; Indryani; Rizki Surya Amanda (JURNAL PENA PAUD, 2026)
Literacy skills in young children, especially those aged 5–6 years, are an important foundation for their readiness to enter the next level of education. However, challenges are still found at the Pelita Doktora Bagan Pete Integrated Islamic Kindergarten (TKIT), Alam Barajo District, Jambi City, where some children have difficulty recognizing letters and associating them with sounds. Therefore, engaging learning media is needed, one of which is the explosion box. This study aims to determine the effect of using the explosion box media on the literacy skills of 5–6-year-old children. This study used a quantitative experimental method with a One Group Pretest-Posttest Design. The sample consisted of 15 children in group B2, selected through purposive sampling. The research instrument was an observation sheet that had been tested for validity. Data analysis was performed through normality tests, homogeneity tests, and hypothesis testing using a paired sample t-test. The results showed a significance value (p-value) < 0.05, indicating a significant difference between the pretest and posttest results. The conclusion of this study shows that the explosion box media has a positive effect on the literacy skills of early childhood, as evidenced by an increase in learning outcomes after treatment. This media can be used as an innovative alternative to support literacy learning for children aged 5–6 years.